Structural-functional and parametric analysis of the social function of pharmaceutical industry - N. O. Tkachenko (Zaporozhye State Medical University, 2016)
Pharmacy has always had a special (social) value and was sensitive to the new social changes in the society and the state. These changes allow better understand the issues associated with increasing the efficiency of pharmaceutical care to the population. The aim of the work: identify, justify and to summarize the main elements of the social function of pharmacy, as a component of health care system, to further evaluate the properties of the pharmaceutical industry as a system. Materials and methods. To achieve this goal the principle of a systematic approach and the complex of research methods such as structural, functional and parametric analysis, logical knowledge and comparison, ad also generalization have been used. As materials of research, we used the results of fundamental and applied research of national and foreign experts on the issue. Results and discussion. The basic principles of the welfare state and pharmacy as socially oriented sectors of the economy have been determined. We have found that the pharmaceutical industry is an agent, which implements a number of elements of the social function, such as pharmaceutical assistance to the population, the production of social goods (drugs, medical products, medical cosmetics, etc.), creating and providing of working places, paying taxes (replenishment of the state budget), the formation and development of human capital, research and innovation activities, charity and sponsorship, environmental protection. Ukraine formally acceded to United Nations document, «Agenda for the XXI Century». This agreement commits our government to implement development and implementation of sustainable development strategies. Its main components are the social responsibility, social integration, an efficient worker and effective owner. Social responsibility acts as a reverse reaction on realization of social policy through the main sectors of the economy. Conclusions. We have summarized the information and substantiated place pharmacy as a component of health care system, in the social sphere of the state. We have identified a list of basic principles and components of the social function of the pharmaceutical industry. We revealed the essence of each component of social pharmacy functions to further evaluate the properties of the pharmaceutical industry as a system. We have proved that Social responsibility acts as a reverse reaction on realization of social policy through the main sectors of the economy (including pharmacy).